INTELLECTUAL CAPITAL VERSUS BALANCED SCORECARD - Ulum, Ihyaul (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
Analyzing texts about balanced scorecard and intellectual capital, the paper discusses not the obvious similarities – that they are both integrated performance management systems – but four more aspects: strategy, organization, management, and indicators. Comparing these four dimensions the paper discusses the differences arising from the very different theories of strategy that they presuppose: competitive advantage versus competency strategy. The paper suggests that the very different notions of strategy that underpin the balanced scorecard and the intellectual capital approach make such comprehensive performance management systems behave in very different ways – the difference between a tightly coupled and a loosely coupled system accounts for this.